Synthesis of carbon nanotubes using biochar as precursor material under microwave irradiation. (15th August 2019) - Hildago-Oporto, Pamela; Navia, R.; Hunter, R.; Coronado, G.; Gonzalez, M.E.
Abstract: Biochar is a carbon-rich porous material obtained by the thermochemical treatment of biomass. Biochar presents a suitable composition as precursor material for carbon nanotubes (CNTs) growth, and can be used as a sustainable alternative in the valorization of biomass. In this study, the synthesis of CNTs using biochar as biological precursor material is presented. CNTs were synthesized using a mixture of biochar and ferrocene including microwave assisted heating. Biochar samples used in the synthesis of CNTs were obtained from agroindustrial waste such as wheat straw, oat hulls, rapeseed cake and hazelnut hulls pyrolyzed at 400 °C and 600 °C. Synthesized CNTs were examined by dynamic light scattering, UV-VIS spectroscopy, Raman spectroscopy and transmission electron microscopy. The results indicate that the physicochemical properties of CNTs were influenced by pyrolysis temperature of biomass. Biochars obtained at 600 °C produced higher CNTs concentration and smaller hydrodynamic diameter. Moreover, CNTs synthesized from biochar of hazelnut hulls and wheat straw show a higher degree of wall graphitization, suggesting superior CNT quality. The results of this study show the feasible production of CNTs using biochar as precursor material. Highlights: Biochar as biological precursor in the synthesis of carbon nanotubes ( CNTs ). Synthesis of carbon nanotubes ( CNTs ) by microwave assisted heating using biochar. A graphitic structure of nanotubes was obtained using biochar as precursor material. The predominant role of pyrolysis temperature on biochar properties was addressed.